(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Ensuring the perspective of the independent Republic of Uzbekistan at the level of world development is connected with major changes in the economic, social, political and cultural spheres. Participation in such changes requires people to have a high level of general and special knowledge, high culture, spirituality and a broad worldview. Reconstruction of the educational system based on these requirements will serve to meet the needs of the society in the field of education of the future generation.